Kepatuhan Siswa Sekolah Dasar Terhadap Pedoman Gerakan 24 di Kabupaten Pringsewu Tahun 2023 - Wicaksono, Lungit; Safei, Imam (Institut Teknologi Bandung, 2024)
The Covid-19 pandemic has caused a crucial reduction in the need for physical education and interaction time in physical activity, so this has become a challenge for all teachers in schools. The aim of this research is to investigate 24-hour movement guidelines between pandemic vs. post-pandemic. The method used in this research is cross sectional with an observational approach. The total subjects in this study were 620 elementary school students with an average age of 10.87 ± 0.51 years, weight 37.12 ± 8.37 kg, and height 140.11 ± 4.73 cm. The results of the research show that after the pandemic, children's outdoor play habits and sleep duration increased sharply as time in front of the screen decreased, although they tended to be the same as conditions during the pandemic. It is hoped that these findings can be a reference for parents and teachers in schools to implement a healthy lifestyle by prioritizing physical activity compared to screen use. so that habits during the pandemic can be overcome and students can increase their level of fitness